Studi Susut Energi pada Jaringan Tegangan Rendah Wilayah Banyuanyar dengan Objek Pelanggan Residensial - Wicaksono, Hary Setiawan; , Umar, ST., MT (2017)
Electricity usage in Indonesia is really needed to put on concern by PT PLN. State Electricity Company (PLN) is a company which has authority in governing the electricity flow in Indonesia, but PLN has an obligation to provide electricity for all Indonesian. Method in this research by studying the literature, data retrieval, manage the data obtained, analyze data, and the latter is a research report. Residential customer is one of the biggest customers, therefore it needs to be reviewed the impact of the decrease by residential customer in low voltage network. The low voltage network in Banyuanyar has maximum transformator distribution capacity of 59 kVA and 100% load as much as 227,27 A and when the load is 80% is as much as 181,81 A, when the load is 60% is as much as 136,36 A. Residential customer RI (450-900 VA) as much as 85,42% and customer R1 (1300-2200 VA) as much as 14,08%, while for subcribers S1 as much as 0,50%. The decrease happens at low voltage network with 100% load is 6.922/98 watt and when the load is 80% is 4.432,03 watt and when the load is 60% is 2.505/28 watt. There is also nontechnical decrease is 3380 watt. Banyuanyar region suffered losses amounting to 4.983,855 kwh energy when the load is 100%, amounting to 3.191,061 kwh when the load is 80%, and amounted to 1.803,801 time load of 60%, while non-technical losses amounted to 1.216,8 kwh.